ЭФФЕКТИВНОСТЬ ЯДЕРНО-МАГНИТНЫХ ИССЛЕДОВАНИЙ ПРИ ПОИСКАХ, РАЗВЕДКЕ И РАЗРАБОТКЕ МЕСТОРОЖДЕНИЙ НЕФТИ И ГАЗА - Кононенко И.Я.; Белорай Я.Л. (My University, 2006)
Nuclear Magnetic Resonance (NMR) analysis of rocks (sludge, core) and fluids in course of drilling allows enhance the geoinformation support and optimize the construction of oil and gas wells. Direct correlation of Nuclear Magnetic Logging in the Earth's magnetic field and content of mobile pore fluid in rocks regardless of lithology provides a direct identification of oil-and-gas reservoirs and estimation of heterogeneous structure of reservoirs. Prompt NMR samples acquired in operating wells which give information about the properties of fluids and state of a reservoir, allows refine geological and filtration models of the reservoir. This model provides source data for drawing a production project.
Keywords: 550.832.582:553.98